Choral voices : ethnographic imaginations of sound and sacrality - Chatterjee, Sebanti (New York: Bloomsbury Academic, 2023)
"The first account of the public life of choral music shaped by imperialistic, cosmopolitan and indigenous characteristics in the regions of Goa in Western India and Shillong in the North-Eastern part of India"--
Prologue. Warming Up -- Introduction. Choral beginnings : Inside the chapel and a home studio -- Making of the Indigenous -- From Loft to the Recording Studio : Shillong Diaries -- The Language of Music : Notes from a Goan Seminary -- Mapping Choral Voices : Role of People and Places -- Tutti : Concluding Section.
Includes bibliographical references and index.
Keywords: Choirs (Music) -- India -- Goa (State); Choirs (Music) -- India -- Shillong; Choral music -- India -- History and criticism; Music -- India -- Western influences; India -- Colonial influence